1991
DOI: 10.1051/alr:1991004
|View full text |Cite
|
Sign up to set email alerts
|

Review of the reproductive physiology of the scallop,Pecten maximus, applicable to intensive aquaculture

Abstract: This paper presents a summary of information on reproduction biology in the scal/op, Pecten maximus, which is required for the sucoessful reseeding and intensive aquaculture programs developed in France since 1982. Data are presented on the following subjccts: environmental factors that sustain gametogenic activity and the lime of year this activity occurs; biochemical changes that are associated with gametogencsis; the consistency of egg quality; and developmcnt of a simple test to prcdict egg quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…However, in normal conditions, C. gigas eggs contain sufficient reserves (particularly essential PUFA) to ensure survival throughout embryogenesis, although not for subsequent larval growth (Utting & Millican 1997). Devauchelle and Mingant (1991) reported that the fecundity of the hermaphroditic scallop P. maximus at similar gametogenic stages decreased with feeding levels. Gonad activity suffered first at lower feeding levels, but only in the female part of the gonad.…”
Section: Feeding Broodstockmentioning
confidence: 99%
“…However, in normal conditions, C. gigas eggs contain sufficient reserves (particularly essential PUFA) to ensure survival throughout embryogenesis, although not for subsequent larval growth (Utting & Millican 1997). Devauchelle and Mingant (1991) reported that the fecundity of the hermaphroditic scallop P. maximus at similar gametogenic stages decreased with feeding levels. Gonad activity suffered first at lower feeding levels, but only in the female part of the gonad.…”
Section: Feeding Broodstockmentioning
confidence: 99%
“…Nevertheless, artificial reproduction of great scallop is poorly controlled in hatcheries: highly variable results were recorded after thermal shocks ). Furthermore, information on sperm biology remains limited (Devauchelle and Mingant 1991;Andersen et al 2011). In this species, spermatozoa released through the ducts, after intragonadal serotonin injection or thermal shock, can be activated when diluted in seawater, and simultaneously a high respiration rate is initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, induced spawning of several mollusks species has been achieved during culture through manipulation of certain variables such as photoperiod, temperature, and diet (Uki and Kikuchi 1984;Devauchelle and Mingant 1991). It is important to study oocytes quality in terms of these variables in order to understand the conditions in which more resistant larvae could be obtained.…”
Section: Discussionmentioning
confidence: 99%